2018
DOI: 10.1111/apm.12823
|View full text |Cite
|
Sign up to set email alerts
|

IL‐10 polymorphisms and T‐cell subsets could affect the clinical presentation and outcome of childhood immune thrombocytopenia in Egyptian population

Abstract: The aim is to study IL-10 polymorphisms and IL-10 level and assess their relation to T-cell subsets in childhood immune thrombocytopenia (ITP). In all, 40 (25 acute, 15 chronic) ITP child patients were investigated at time of presentation, compared to 15 healthy, age- and gender-matched controls and followed up for 1 year to determine chronic cases. Studying the effect of IL-10 promoter polymorphism was done by PCR-RFLP, IL-10 level was determined by ELISA, natural killer cells and T-cell subsets were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…The possible involvement of this cytokine in ITP has been deeply investigated over the years. In particular, several authors found a correlation between the IL-10 (-1082) polymorphism, which is associated with an impairment in general cytokine release, and the acute form of ITP [36,37,38,39,40]. It is known that both CB1 and CB2 receptors can influence the production of IL-10.…”
Section: The Ec System In Immune Thrombocytopeniamentioning
confidence: 99%
“…The possible involvement of this cytokine in ITP has been deeply investigated over the years. In particular, several authors found a correlation between the IL-10 (-1082) polymorphism, which is associated with an impairment in general cytokine release, and the acute form of ITP [36,37,38,39,40]. It is known that both CB1 and CB2 receptors can influence the production of IL-10.…”
Section: The Ec System In Immune Thrombocytopeniamentioning
confidence: 99%
“…49,50 The presence of these polymorphisms can disturb the tolerance of the immune system to its antigens. 51,52 We discuss several studies on IL-10 polymorphisms in ►Table 7.…”
Section: Discussionmentioning
confidence: 99%
“…11,25 The TT genotype carriers of IL-10 rs1800896 and rs1800872 were reported to be lined with lower proportion of CD4 cells and higher proportion of CD8 cells, lower CD4/CD8 ratio and lower T-reg frequency. 28,29 The imbalance of lymphocyte subsets reflected a dysregulated state of immune system, which was predominantly involved in AA. 4,30 Our results accordingly showed that rs1800896 TT genotype was positively associated with AA susceptibility compared with CT + CC carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The production of IL‐10 was considered to be strongly influenced by the genetic background and had pleiotropic effects on the immune system, the A‐A‐G‐C‐C haplotype is associated with decreased production of interleukin‐10 while the T‐C‐A‐T‐A haplotype is defined by high levels of interleukin‐10 11,25 . The TT genotype carriers of IL‐10 rs1800896 and rs1800872 were reported to be lined with lower proportion of CD4 cells and higher proportion of CD8 cells, lower CD4/CD8 ratio and lower T‐reg frequency 28,29 . The imbalance of lymphocyte subsets reflected a dysregulated state of immune system, which was predominantly involved in AA 4,30 .…”
Section: Discussionmentioning
confidence: 99%